PERAN GURU PAI DALAM MENINGKATKAN KUALITAS BERAGAMA SISWA DI SMK NURUL HIDAYAH AL FALAH PUNGGING MOJOKERTO - Muslih, Imam (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article describes the role of PAI teachers in improving the religious quality ofstudents at SMK Nurul Hidayah Al Falah Pungging Village, Mojokerto Regency. With aqualitative descriptive approach, the data collection techniques use observation, interviews, anddocumentation, the researcher analyzed by the Miles and Hubberman analysis techniques, datareduction, data display, and conclusion, the research gave results that the quality of religiousstudents, can be seen from everyday morals, both in terms of speech, behavior, and charactertowards teachers and friends. Honesty which is the principle of faithful people reflected ineveryday school life. Through habituation activities, the role of PAI teachers is to oversee theprogram and make these activities a good habit which includes scheduled/routine, spontaneous,and caring activities. The role of PAI teachers in habituation activities can be seen from the resultsof students' behavior and responses to programs/activities related to improving the religiousquality of students from time to time. SMK Nurul Hidayah Al Falah Pungging has adequatefacilities and infrastructure to support the program, but external factors often become obstacles,especially the freedom of students to access the internet, especially outside school hours. PAIteachers make an effort, one of them is to approach emotionally, habituate in religious activitiesand become a good example for students in the SMK Nurul Hidayah Al Falah Pungging, until theefforts made are in accordance with what is expected Keywords: PAI Teacher's role, habituation, religious quality